Fluid‐Structure Interaction Simulations of Aortic Dissection - Schussnig, Richard; Rolf-Pissarczyk, Malte; Holzapfel, Gerhard A.; Fries, Thomas-Peter (Proceedings in Applied Mathematics and Mechanics, 2021)
The numerical modeling of aortic dissection (AD) is a particularly challenging biomechanical application, since the underlying coupling of tissue deformation and blood flow has to be considered, leading to a fluid-structure interaction (FSI) problem. To improve clinical relevance, patient-specific data and state-of-the-art constitutive models have to be incorporated. Computational methods to consider for tissue prestress and fiber orientation are presented herei